(untitled) (Global Journal of Human-Social Science, 2019)
This paper seeks to examine the constraints litigants face in seeking to reap the benefits of judgments obtained from a superior court of record, through garnishee proceedings particularly when the funds to be garnished are in the custody of a public officer and especially where the valid judgement entered is against an organ of the government. It looks at whether the attorney general would readily grant the consent especially when he is also a party to the suit. The paper finally appraised the divergent views of the appellate court with regards the constitutionality or otherwise of the consent of the attorney general before attaching the funds in the hands of a public officer.